2021
DOI: 10.3389/fpls.2020.616077
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ion Transport Across Plant Membranes by Polyamines: Understanding Specific Modes of Action Under Stress

Abstract: This work critically discusses the direct and indirect effects of natural polyamines and their catabolites such as reactive oxygen species and γ-aminobutyric acid on the activity of key plant ion-transporting proteins such as plasma membrane H+ and Ca2+ ATPases and K+-selective and cation channels in the plasma membrane and tonoplast, in the context of their involvement in stress responses. Docking analysis predicts a distinct binding for putrescine and longer polyamines within the pore of the vacuolar TPC1/SV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 196 publications
1
19
0
Order By: Relevance
“…Al-Hassan et al [ 34 ] concluded that family Plantaginaceae have a “constitutive mechanism” of tolerance in which the transport of Na + and Cl − ions (inorganic osmolytes) to the leaves and compartmentalization in the vacuole, contribute to cellular osmotic balance, and increase antioxidant metabolism under saline stress [ 34 , 36 ]. Polyamines are related to ionic transport through at membrane thylakoid, tonoplast, and plasma membranes [ 52 , 62 , 63 ]. Pottosin and Shabala showed that exogenous PAs application (0.1–1 mM) activated Ca 2+ efflux, net H + fluxes, and activated H + -ATPase pump under stress, but all these experiments were realized in the roots of glycophyte seedlings [ 52 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Hassan et al [ 34 ] concluded that family Plantaginaceae have a “constitutive mechanism” of tolerance in which the transport of Na + and Cl − ions (inorganic osmolytes) to the leaves and compartmentalization in the vacuole, contribute to cellular osmotic balance, and increase antioxidant metabolism under saline stress [ 34 , 36 ]. Polyamines are related to ionic transport through at membrane thylakoid, tonoplast, and plasma membranes [ 52 , 62 , 63 ]. Pottosin and Shabala showed that exogenous PAs application (0.1–1 mM) activated Ca 2+ efflux, net H + fluxes, and activated H + -ATPase pump under stress, but all these experiments were realized in the roots of glycophyte seedlings [ 52 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are related to ionic transport through at membrane thylakoid, tonoplast, and plasma membranes [ 52 , 62 , 63 ]. Pottosin and Shabala showed that exogenous PAs application (0.1–1 mM) activated Ca 2+ efflux, net H + fluxes, and activated H + -ATPase pump under stress, but all these experiments were realized in the roots of glycophyte seedlings [ 52 , 62 , 63 ]. There are no studies on the application of PAs in halophytes on membrane ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2019) also reported that GABA can reduce the Na + /K + ratio by inducing polyamine generation to enhance salinity-alkalinity stress tolerance in muskmelon. Polyamines were reported to assist in the movement and sequestration of Na + from the cytoplasm to the vacuole and affect K + flux by amending outward-and inward-rectifying K + channels in guard cells and root cells (Pál et al, 2015;Pottosin et al, 2020). Moreover, the application of plant growth-promoting rhizobacteria showed an enhanced capacity to counteract salinealkaline stress in Chrysanthemum plants, which can modify cellular abscisic acid levels, inhibit net K + efflux and concurrently induce net Na + efflux by modulating several Na + /H + and K + antiporters/channels (Zhou et al, 2017).…”
Section: Maintaining Na + -K + Ion Balance Via Channel Proteins and Transportersmentioning
confidence: 99%
“…Many findings have demonstrated the important properties of these polycations. Among such properties, polyamines appear to take part in the control of the translation elongation procedure through the Ser/Thr kinases implicated in the phosphorylation of translation elongation factors process, in the control of ion channels gating and in the regulation of oxidative processes [20][21][22][23][24][25]. Moreover, these natural organic compounds are able to control gene expression by modifying the DNA and RNA structure.…”
Section: Introductionmentioning
confidence: 99%